Effectivness of the Adoption of the XBRL Standard in the Indian Banking Sector - Purnendu Kumar; S. Sujeesh Kumar; Archana Dilip (Journal of Central Banking Theory and Practice, 2019)
The XBRL standard was adopted by the Reserve Bank of India (RBI) in the year 2008 as a standard by which the banks that are regulated by the RBI submit regulatory, prudential, supervisory, and other statistical data. This study focuses on estimating the effectiveness of the adoption of the XBRL standard in the Indian banking sector. The effectiveness has been studied on the basis of the responses received on the survey conducted targeting the commercial banks of India. Two important factors, namely, `Effectiveness of the XBRL Data Submission' and `Savings of Time and Cost' have been considered mainly for the study. The study revealed that the overall efficiency of the reporting system in the Indian banking sector has increased to a great extent with the adoption of the XBRL standard. Although the overall effectiveness of XBRL adoption has been found to be satisfactory, there is always room for further enhancement of the system in order to achieve complete effectiveness.
Keywords: O33; Q55; G21; 330; XBRL; ADF; Technology; Effectiveness; Survey etc.